The Implementation of Flipped Classroom in EFL Reading During Covid-19 Pandemic: Indonesian EFL Students’ Voices - Nursyahdiyah, Nursyahdiyah; Dalimunte, Ahmad Amin; Daulay, Sholihatul Hamidah (ENGLISH FRANCA : Academic Journal of English Language and Education, 2022)
The purpose of this study was to explore students' voices on the implementation of the flipped classroom in the EFL Reading Class during the Covid-19 pandemic. This research was a case study using a qualitative descriptive method. The participant of this study were students of grade 10 that consist of 32 students at one Islamic Senior High School (Madrasah Aliyah Negeri) in North Sumatra. The results of this study are the improvement of quality of learning EFL Reading through the flipped classroom strategy, an increase in students' independence learning in using the flipped classroom utilizing technology in the flipped classroom also has a positive impact on the role of technology in education. Based on the finding in this research, the implementation of the flip classroom during the pandemic can be one of the reference methods that can be used by teachers by considering the benefits of the flipped classroom for students, such as making it easier to access and students' readiness to face learning.Â